A classroom SNS to promote reflective activity in programming learning for children - Kumpei Tsutsui; Hideyuki Takada (The Asia-Pacific Society for Computers in Education (APSCE), 2018)
Abstract ■■■ In recent years, workshops involving programming on computers have been held in elementary education to promote creative thinking. In our experience of conducting programming workshops for children for over 10 years, we cannot have enough time to let them share and reflect on their creative activity, although reflection is one of the important factors for successful experience-based learning. In order to solve this problem, we have developed a classroom SNS (social networking service) system for children to upload a post and share their project. On the SNS site, they can upload three kinds of contents: action view, code view, and comments. We conducted an experiment to examine if children have performed the sharing and reflection activity with the SNS system during a programming workshop. The result shows that the SNS system would promote motivation for children to reflect on their project.